EU CONVERGENCE: A PATHWAY TO ECONOMIC STABILITY - Adrian LUNGU; Mihai Daniel ROMAN; Diana Mihaela STANCULESCU (Eastern European Journal of Regional Studies)
In the context of global systemic transformations, economic security has become a focal point in political and economic debates. The article explores how economic convergence within the European Union (EU) contributes to strengthening regional economic security. Using an innovative approach based on cluster analysis, the study reveals economic convergence trends among EU member states, highlighting the involvement of this process in promoting economic stability and security in the era of systemic changes. Our methodology involves applying clustering techniques to an extensive set of economic indicators to assess the dynamics of economic convergence between EU countries over the last two decades. The cluster analysis carried out allowed the grouping of countries based on their similar economic characteristics, thus providing a clear picture of the progress towards convergence. The results indicate a strong trend of economic alignment within the EU, with the formation of clusters suggesting a reduction in economic discrepancies. This process of convergence not only reflects greater economic cohesion, but also contributes to the macroeconomic stabilization of the region, an important aspect for economic security in the face of global volatility and uncertainties. The analysis shows that the EU is moving towards uniformity and economic convergence, with economic clusters becoming more similar over time.